2013
DOI: 10.1016/j.bbagen.2012.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactors to influence stem cell fate: Augmentation of mesenchymal stem cell signaling pathways via dynamic culture systems

Abstract: Background Mesenchymal stem cells (MSCs) are a promising cell source for bone and cartilage tissue engineering as they can be easily isolated from the body and differentiated into osteoblasts and chondrocytes. A cell based tissue engineering strategy using MSCs often involves the culture of these cells on three-dimensional scaffolds; however the size of these scaffolds and the cell population they can support can be restricted in traditional static culture. Thus dynamic culture in bioreactor systems provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 149 publications
(157 reference statements)
1
83
0
Order By: Relevance
“…Using these cells also avoids the ethical ambiguities like using embryonic stem cells. 17 Several previous studies also demonstrated that mesenchymal stem cells could recruit to injured tissue and generate high levels of cytokines and growth factors 18,19 and play a repair role. Therefore, it is interest to determine whether MSCs can be tracked in vivo with non-invasive imaging after AKI stem cells treatment, which will provide a tool for the development and testing of optimal AKI-specific treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Using these cells also avoids the ethical ambiguities like using embryonic stem cells. 17 Several previous studies also demonstrated that mesenchymal stem cells could recruit to injured tissue and generate high levels of cytokines and growth factors 18,19 and play a repair role. Therefore, it is interest to determine whether MSCs can be tracked in vivo with non-invasive imaging after AKI stem cells treatment, which will provide a tool for the development and testing of optimal AKI-specific treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mitogen-activated protein kinase signaling, including ERK1/ 2, p38, and c-Jun N-terminal kinase pathways, are influenced by shear stress through the cell surface signaling to activate the GTPase. 113 Novel design of bioreactors that provide homogenous shear stress may be required in the formation and expansion of MSC aggregates. Spinner flasks displayed heterogeneous shear stress (0-2.83 dyn/cm 2 ), fluid velocity, and Kolmogorov eddy size, which may limit their biological effects on MSCs.…”
Section: D Msc Aggregates: Mechanisms Properties and Applicationsmentioning
confidence: 99%
“…This culture system environment is externally controlled by the incubator environment (O 2 , pH, and humidity) but agitation is controlled in terms of velocity and type of impeller. 2,3 It has been widely explored for the culture of suspension cells, and in some cases for attachment-dependent cells in the form of cell aggregates 4,5 or cell-loaded microcarriers. 3,[6][7][8][9] However, only a few studies described the use of spinner flasks for cell cultures in three-dimensional (3D) scaffolds.…”
mentioning
confidence: 99%
“…1,2 Spinner flasks are probably the simplest dynamic culture systems commercially available. They have been used for long times in cell culture, and they are the first step when it comes to scale up the classical two-dimensional (2D) cell culture.…”
mentioning
confidence: 99%
See 1 more Smart Citation